Enhanced pharmacokinetic and therapeutic of GSH-responsive mPEG-b-P(HPMA)-SGI1776 conjugate for osteosarcoma - Shi, Xingchen; Wang, Rourou; Zhang, Zhenghua; Wang, Zixuan; Xu, Weibing; Shi, Xinhe; Geng, Zhe (Frontiers in Pharmacology, 2025)
IntroductionSGI-1776 represents the first serine/threonine kinase inhibitor to be utilized in the treatment of osteosarcoma. It is severely restricted by poor aqueous solubility, short degradation half-life and severe side effect.MethodsA polymeric prodrug is prepared by covalently embedding SGI-1776 into mPEG-b-P(N-(2-hydroxypropyl) methylacrylamide) carrier via GSH-responsive disulfide bond. The chemical composition and assembly properties of the conjugate are characterized.ResultsThe loading capacity of SGI1776 in the conjugate is 22%. The conjugate displays a typical spherical nanoparticle with diameters around 150–260 nm. Cumulative release amounts of SGI1776 can be detected to be 52.9% at the concentration dithiothreitol of 20 mM at 24 h. The hemolysis rate is about 2.35% even when the concentration increases up to 1,000 mg/L. The value of IC50 is about 18.8 μg SGI1776 equiv. per mL for 143b cells.DiscussionThe conjugate is more likely to induce apoptosis and can be blocked 143b cells in the S cycle phase. The maximum plasma concentration of the conjugate is attained 0.52 ± 0.092 μg/mL at 4 ± 0 h after the oral administration. The conjugate exhibits better lysosomal escape ability, biocompatibility.